Realization of an dimmable electronic ballast for a discharge lamps fed by an LSCSCP circuit and a PFC stage - Marref Mohammed Amine; Hamdaoui Habib; Seyf Eddine Bechekir (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presents an electronic ballast for discharge lamps. The ballast consists of two stages: i) a boost-buck chopper that performs the power factor correction and provides an approximately variable DC link voltage to drive the second stage and ii) a half-bridge MOSFET inverter with an improved series-parallel inductor-capacitor-inductor (LsCpLp) resonant circuit to drive the high-frequency discharge lamp. The electronic ballast designed here is a multi-purpose ballast which was experimentally tested for high-pressure sodium discharge lamps 150 W and metal halide lamps 150 W. It was revealed that this mode of operation makes it possible to vary and dim the light of the lamp and to improve the quality of the power supply while reducing the harmonic currents in networks.